EFFICACY OF ENDOSURGICAL CORRECTION OF FEMALE OVARIAN INFERTILITY - G.A. Tanish; G.S. Babadjanova (Central Asian Journal of Medicine, 2023)
In this study, a comprehensive examination of women with infertility based on clinical, biochemical, and ultrasound methods was carried out. In total, 60 women with infertility who were admitted to the clinic of the Balkh University, Mozori-Sharif, Afghanistan, were examined. Patients were divided into 2 groups - with PCOS and a combination of PCOS with menstrual dysfunction. Conducted a comprehensive treatment to correct the identified hormonal disorders. In the absence of the effect of conservative treatment, endosurgical treatment was performed. The effect of treatment was higher with complex treatment and, if necessary, the use of assisted reproductive technologies.